2021
DOI: 10.1080/17588928.2021.1906638
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the emotional valence of future thoughts

Abstract: Affective future thinking allows us to prepare for future outcomes, but we know little about neural representation of emotional future simulations. We used a multi-voxel pattern analysis to determine whether patterns of neural activity can reliably distinguish between positive and negative future simulations. Neural patterning in the anterior cingulate and ventromedial prefrontal cortices distinguished positive from negative future simulations, indicating that these regions code for the emotional valence of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…showed that the vmPFC tracked the perceived pleasantness of de novo simulations involving the integration of disparate familiar autobiographical elements—a pattern that emerged while controlling for the pleasantness of the individual elements. Other work shows that the vmPFC, as well as the anterior cingulate cortex (in a region of interest spanning dorsal and ventral components), codes for the emotional valence of both positive and negative future simulations 67 . We note that the function of the vmPFC is historically debated, as its role in cognition is complex and multifaceted (often associated with high‐level terms, such as emotion , value , schema processing , etc.).…”
Section: Neural Correlates Of Emotional Imaginationmentioning
confidence: 79%
See 4 more Smart Citations
“…showed that the vmPFC tracked the perceived pleasantness of de novo simulations involving the integration of disparate familiar autobiographical elements—a pattern that emerged while controlling for the pleasantness of the individual elements. Other work shows that the vmPFC, as well as the anterior cingulate cortex (in a region of interest spanning dorsal and ventral components), codes for the emotional valence of both positive and negative future simulations 67 . We note that the function of the vmPFC is historically debated, as its role in cognition is complex and multifaceted (often associated with high‐level terms, such as emotion , value , schema processing , etc.).…”
Section: Neural Correlates Of Emotional Imaginationmentioning
confidence: 79%
“…Beyond the hippocampus, the literature suggests a role of the vmPFC-another DN MTL node-in evaluative aspects of imagination, namely, appraising the affective significance of an event. 28,29,63,[66][67][68] In one clever study, Benoit et al 28 showed that the vmPFC tracked the perceived pleasantness of de novo simulations involving the integration of disparate familiar autobiographical elements-a pattern that emerged while controlling for the pleasantness of the individual elements. Other work shows that the vmPFC, as well as the anterior cingulate cortex (in a region of interest spanning dorsal and ventral components), codes for the emotional valence of both positive and negative future simulations.…”
Section: Neural Correlates Of Emotional Imaginationmentioning
confidence: 99%
See 3 more Smart Citations